Investigating the Role of Green Supply Chain on Sustainable Development in Parsian Gas Refinery - Rahimi, Habibe; Askari, Ahmad; Zeinoddin, Sara (IJRDO - Journal of Applied Management Science, 2018)
The purpose of this research is to investigate the role of green supply chain management on sustainable development in Parsian gas refinery. The present research is an applied and descriptive survey method. The statistical population of this research is 105directors, senior managers, operational managers and intermediate managers. In this research, the non-inferential improvement of the judgment method was used to determine the sample. The data gathering tool in this study is a standard two-part questionnaire on green supply chain management and sustainable development (Rahmani, 2015). Validity of the questionnaires based on expert's view and their reliability based on Cronbach's alpha coefficient for green supply chain questionnaire was 0.838 and for Sustainable Development Questionnaire was 0.903. The research method was linear regression analysis. The results of this research indicate that the dimensions of green supply chain management have a positive and significant effect on the sustainable development dimensions in Parsian gas refinery.